Improving infant formulas: on the way to approaching breast milk - I. N. Zakharova; Y. A. Dmitrieva; E. A. Gordeeva (Медицинский совет, 2016)
Breast milk is the gold standard of infant feeding during the first year of life that ensures adequate physical and psychological development. The composition of human milk changes all the time in the process of one feeding as well as throughout the whole period of lactation. The ingredients of breast milk promote the normal growth of the baby, affect postnatal differentiation of tissues, the formation of the central nervous system (CNS), auditory and visual analyzers, development of the intestinal microbiota of the infant. Breastfeeding contributes to a strong psycho-emotional bond between mother and child which provides the best conditions for further development of the mind, intelligence and behavioral characteristics.